Comprehensive analysis of a novel three‐phase multilevel inverter with minimum number of switches. Issue 8 (1st June 2016) - Raushan, Ravi; Mahato, Bidyut; Jana, Kartick Chandra
Abstract : A novel and generalised three‐phase multilevel inverter (MLI) with a minimum number of switches have been proposed. The number of voltage levels can be increased to a significant value by incorporating few switches and the DC voltage sources. In the proposed three‐phase MLI, the number of phase‐voltage levels can be increased twice as the number of switches increased. The detailed analysis of the proposed MLI, mathematical modelling of the inverter voltage and the switching loss calculation have been done for a seven‐level inverter. Modelling and simulations of the proposed generalised three‐phase inverter are carried out using MATLAB/SIMULINK. The simulation results of the proposed multilevel configuration corresponding to the different voltage levels as well as at different modulation index are presented. A laboratory prototype of the proposed five‐level inverter has been developed and tested for the speed control of an induction motor. The experimental results for the different modulation indexes are presented, that verifies the simulation results. A detailed comparison of the proposed MLI with the other popular multilevel configuration is presented to reflect the merits of the proposed structure for the reduced component count.